2020
DOI: 10.1038/s41598-020-74518-7
|View full text |Cite
|
Sign up to set email alerts
|

Biorheology of occlusive thrombi formation under high shear: in vitro growth and shrinkage

Abstract: Occlusive thrombi formed under high flow shear rates develop very rapidly in arteries and may lead to myocardial infarction or stroke. Rapid platelet accumulation (RPA) and occlusion of platelet-rich thrombi and clot shrinkage have been studied after flow arrest. However, the influence of margination and shear rate on occlusive clot formation is not fully understood yet. In this study, the influence of flow on the growth and shrinkage of a clot is investigated. Whole blood (WB) and platelet-rich plasma (PRP) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…Decreased platelet contractility is associated with the abnormal mechanics of blood clots. Several studies have confirmed the high relevance of platelet contractile forces to platelet aggregation and the subsequent hemostasis (Li and Li, 2006;Muthard and Diamond, 2012;Muthard and Diamond, 2013;Ting et al, 2013;Chen Z et al, 2019;van Rooij et al, 2020). Lam et al (2011) customized a side-view atomic force microscope (AFM) to measure the contractile force of a single platelet encapsulated between the fibrinogen-coated cantilever and surface.…”
Section: Microfluidic Devices That Gauge Platelet Contractile Forcementioning
confidence: 97%
“…Decreased platelet contractility is associated with the abnormal mechanics of blood clots. Several studies have confirmed the high relevance of platelet contractile forces to platelet aggregation and the subsequent hemostasis (Li and Li, 2006;Muthard and Diamond, 2012;Muthard and Diamond, 2013;Ting et al, 2013;Chen Z et al, 2019;van Rooij et al, 2020). Lam et al (2011) customized a side-view atomic force microscope (AFM) to measure the contractile force of a single platelet encapsulated between the fibrinogen-coated cantilever and surface.…”
Section: Microfluidic Devices That Gauge Platelet Contractile Forcementioning
confidence: 97%
“…In a shear gradient context, it was observed that VWF unfolding increased at two-fold lower flow rates when compared to constant shear flows (Zhang, 2009;Sing and Alexander-katz, 2010). Corresponding studies revealed that rapid alterations of the flow through shear microgradients promoted discoid platelet aggregation in the post-stenotic region, or micro-vessel curvatures (Nesbitt et al, 2009;Rooij et al, 2020;Spieker et al, 2021). It suggests that the rapid decrease in shear rate restructures the filamentous membrane tethers and allows integrins α IIb β 3 to considerably stabilise the aggregate.…”
Section: Disturbed and Elongated Shear Rate: Microgradientsmentioning
confidence: 99%
“…Activated platelets in newly formed aggregates are highly contractile with respect to thrombus stabilization and consolidation (76)(77)(78)(79)(80)(81). Recent studies have sought to analyze the degree of forceful cytoskeletal contractions in activated platelets.…”
Section: Platelet Contractionmentioning
confidence: 99%